The impact of assertive outreach teams on hospital admissions for psychosis: a time series analysis. Issue 7 (29th June 2015) - Hamilton, I.; Lloyd, C.; Bland, J. M.; Savage Grainge, A.
<x xml:space="preserve">Abstract</x> Accessible summary Although the assertive outreach model was developed in the United States and imported to the United Kingdom to date, there is only limited evidence to support its wide‐scale implementation within the United Kingdom. This is the first study to have combined a large dataset with this type of research method to explore the impact of assertive outreach teams on hospital admissions. The introduction and expansion of assertive outreach teams was associated with reducing hospital admissions for people with psychosis. This study found a consistent summer peak in hospital admissions which community and in‐patient mental health nurses should take account of and plan for. Abstract Ever since the Mental Health Policy Implementation Policy Guide paved the way for the introduction of the Assertive Outreach Treatment (AOT) model in England, the impact of this approach has been the subject of considerable debate but limited evaluation. To date, most of the evidence supporting this model has originated from outside the United Kingdom. A central aim of the AOT was to reduce the need for in‐patient treatment. We aimed to assess the impact of the AOT model on hospital admissions for people with psychosis in England. Interrupted time series analysis was used in this study to evaluate the impact of the policy change. Following the introduction of the AOT model, a statistically significant reduction in hospital admissions for psychosis was found. In addition, we observed a repeated, annual summer peak in admissions. This study adds to the international evidence which supports the effectiveness of the AOT model in reducing hospital admissions for people with severe mental health problems. We offer five suggested implications for mental health nurses and clients based on our findings.